Left Circumflex Artery Rupture with Left Atrial Tamponade and Functional Mitral Stenosis - Weiting Huang; Khaled Mohamed Emadeldin Moheb Hammad; Victor Tar Toong Chao; Khung Keong Yeo (Case Reports in Cardiology)
The growth in percutaneous transluminal devices has enabled operators to tackle more complex, native, and post-bypass surgery anatomy. However, complications such as coronary artery dissection, coronary perforation, retrograde aortic dissection, arrhythmias, and acute coronary syndrome still occur with resulting mortality rates of up to 4.2% in complex interventions. Perforation of the circumflex artery is of particular interest in view of its position and relation to the surrounding cardiac structures. This is a site of potential fluid collection, and as the left atrium is fixed to the parietal pericardium at the entry of the pulmonary veins, fluid in the oblique sinus can accumulate enough pressure to compress the left atrium and the coronary sinus. We present a case of left circumflex artery perforation which demonstrates the physiologic complications of coronary sinus and left atrial compression and the resultant functional mitral stenosis.